Orderly deposition of multi‐layer nanofibrous membrane by electrohydrodynamic direct writing. (3rd April 2019) - Zheng, Gaofeng; Zhu, Ping; Jiang, Jiaxin; Zhong, Weizheng; Zheng, Jianyi; Liu, Juan; Wang, Xiang; Li, Wenwang; Guo, Shumin
Abstract : High sensitivity bio‐detection puts forward great requirement on the orderly deposition of multi‐layer nanofibrous membrane within the substrate. Electrohydrodynamic direct writing was utilised to realise the precise deposition of nanofibres, then multi‐layer nanofibrous membrane can be gained by controlling the collector to move at the pre‐designed trajectory repeatedly. How to overcome the fusion between layers has been the key to the orderly deposition of multi‐layer nanofibrous membrane. The deposition and deformation behaviours and optimised controlling strategies of the deposited multi‐layer nanofibrous membrane were studied. The distance between the parallel nanofibres was decreased and a time interval was introduced to adjust the solidification process to overcome the fibre fusion between two adjacent layers. The uniform solid nanofibres without obvious deformation can be printed layer by layer to build the orderly multi‐layer nanofibrous membrane. This work provides an excellent way for the fast fabrication of high sensitivity bio substrate.